ANALYSIS OF THE VALUE – ADDED FOR TAYAN BAUXITE ORE AND CHEMICAL GRADE ALUMINA - Harta Haryadi (Indonesian Mining Journal, 2016)
Research conducted at PT. ANTAM and PT. ICA (Indonesia Chemical Alumina) Tayan, West Kalimantan was aimed to compare the amount of company value-added from selling the bauxite ore as a raw material and the chemical grade alumina as a processed goods. This research showed that company value added from selling 850.000 tons raw meterial US $ 8.92 million it consisted of salary and wages of US $ 692.42 thousand, royalties, CSR and insurance US $ 473.87 thousand, surveyor services US $ 150.00 thousand, other services $ 45.00 thousand, corporate income tax of US $ 1.64 million, Bank interest US $ 191.77 thousand. The company profits obtained the US $ 5, 73 million was. Of the US$ 8.92 million added value and 850.000 bauxite selling, the increase of total added value was US$ 10.49 per ton. Selling the chemical grade alumina up to 300,000 tons or equivalent to 850,000 tons provided the value-added to the US $ 57.24 million that consisted of an increase in revenue salaries and wages to US$ 3.85 million. 50.75 billion, royalties, CSR and insurance of US $ 2.49 million, surveyor services and other services US $ 16.50 million, corporate income tax $ 10.39 million, Bank interest US $ 1.21 million and corporate profits to the US $ 22.00 million. The overall value added from selling the processed goods was US$ 190.44 per ton. It is indicated that selling the chemical grade alumina provides a greater profit than that of selling the raw material.